Russian National technological initiative in the sphere of mineral resource usage (Rudarsko-geološko-naftni zbornik, 2017)
Operating efficiency improvement of the Russian company MMC Norilsk Nickel will be determined by the extended involvement in production of both new geogenic off -balance ores from combine deposits and previously accumulated technogenic mineral raw materials – metallized rock mass dumps and sand tailings. This article proposes a complex program of technological initiative in the sphere of mineral resource usage, and justifi es eff ective measures aimed at developing the city-forming mining and metallurgical industry.